FORMASI SPASIAL PERMUKIMAN INFORMAL DI TPST BANTARGEBANG BERDASARKAN PERILAKU DAN STRATEGI BERTAHAN HIDUP PEMULUNG - Grisella , Grisella; Winata, Suwardana (Jurusan Arsitektur dan Perencanaan, 2025)
The Integrated Waste Treatment Facility (TPST) Bantar Gebang is one of the largest waste management facilities in Indonesia and serves as the primary source of livelihood for thousands of waste pickers. The daily activities and survival strategies adopted by these waste pickers who live near the TPST Bantargebang landfill, have led to the organic emergence of informal settlements surrounding the facility. These settlements are a spatial response to an environment that was never intended to serve as a residential area, yet has evolved into a living space with distinct functional characteristics. This study aims to explore the relationship between the behaviors of waste pickers and the formation of their residential spaces, while also identifying the characteristics of their community, spatial needs, and forms of adaptation to the surrounding environment, in order to recognize spatial patterns embedded in their everyday lives. A qualitative-descriptive approach is employed, using both field observation and remote observation methods, followed by the development of diagrams to analyze daily activities and spatial configurations. The findings reveal that the collective migration patterns of waste pickers, driven by economic factors, shape a socially cohesive structure that is reflected in the spatial organization of their settlements. Economic activities such as sorting, categorizing, and reselling recyclable materials directly influence the formation of workspaces, storage areas, and spatial connectivity between dwellings. This research demonstrates that waste picker settlements are not merely representations of slum conditions, but rather manifestations of adaptive spatial strategies shaped by context. These insights serve as a foundation for developing a more responsive spatial planning approach that addresses the needs of informal communities, particularly waste pickers. Keywords: behavior; informal settlement; landfill; pattern; spatial; waste picker Abstrak Tempat Pengolahan Sampah Terpadu (TPST) Bantar Gebang merupakan salah satu fasilitas pengelolaan sampah terbesar di Indonesia dan menjadi sumber penghidupan utama bagi ribuan pemulung. Aktivitas dan strategi bertahan hidup yang dijalankan para pemulung yang tinggal didekat landfill TPST Bantargebang, telah mendorong terbentuknya permukiman informal yang tumbuh secara organik di sekitar kawasan tersebut. Permukiman ini merupakan respons spasial terhadap lingkungan yang sejak awal tidak dirancang sebagai area hunian, namun kemudian berkembang menjadi ruang hidup dengan karakteristik fungsional yang spesifik. Penelitian ini bertujuan untuk memahami keterkaitan antara perilaku pemulung dan pembentukan ruang tempat tinggal mereka, serta mengidentifikasi karakteristik komunitas, kebutuhan ruang, dan bentuk adaptasi terhadap kondisi lingkungan, guna memperoleh pola yang melekat dalam kehidupan sehari-hari pemulung. Pendekatan yang digunakan adalah kualitatif-deskriptif dengan metode observasi lapangan dan observasi daring, dilanjutkan dengan penyusunan diagram aktivitas dan ruang. Hasil penelitian menunjukkan bahwa pola migrasi pemulung yang terjadi secara kelompok karena dorongan ekonomi membentuk struktur sosial berbasis kebersamaan, yang tercermin dalam konfigurasi spasial permukiman. Aktivitas ekonomi seperti memilah, menyortir, dan menjual kembali material daur ulang turut memengaruhi pembentukan ruang kerja, ruang penyimpanan, serta keterhubungan antarhunian. Penelitian ini menunjukkan bahwa permukiman pemulung tidak semata-mata mencerminkan kekumuhan, melainkan merupakan wujud strategi adaptif yang membentuk ruang secara kontekstual. Temuan ini menjadi dasar untuk merumuskan pendekatan penataan hunian yang lebih responsif terhadap kebutuhan komunitas informal, khususnya pemulung.